Working together: An investigation of the impact of working alliance and cohesion on group psychotherapy attendance. (3rd September 2021) - Clough, Bonnie; Spriggens, Lauren; Stainer, Matthew; Casey, Leanne
Abstract : Objectives: Group psychotherapy holds considerable potential for cost‐effective treatment delivery. However, issues with client attendance can compromise the efficacy of such treatments. To date, client specific factors are amongst the most researched predictors of attendance in psychotherapy, with much less of a focus given to process factors, particularly in the group therapy context. This study aimed to determine which process factors influenced attendance in the context of a group therapy programme for adults with anxiety. It was hypothesized that (1) the working alliance and group cohesion would be moderately correlated, (2) both the working alliance and group cohesion would explain unique variance in session attendance, and (3) the working alliance would act as a moderator for attendance, when group cohesion was low. Design: The study utilized a within participants design. Methods: Participants were 91 adults (aged 18–74 years) who took part in a 9‐week, transdiagnostic cognitive behavioural group therapy programme for the treatment of anxiety disorders. Results: Working alliance and group cohesion were significantly, but only moderately correlated ( r s ranging .41 to .55). Together, working alliance and group cohesion significantly predicted total session attendance (17.70% variance explained). Working alliance did not moderate the relationship between group cohesion and session attendance. Conclusions: The importance of individual and group processes in influencing group therapy engagement is highlighted, including the role of fostering bonds within the group and between clients and therapists. Practitioner points: A complex array of process factors has been argued to influence treatment outcomes in group therapy The quality of the relationship between group therapy clients, as well as the relationship between a client and the therapist, predict session attendance. The quality of the relationship between the client and the therapist may be the most important predictor of session attendance. Therapists should foster positive relationships between each client and the therapist in group therapy, as well as assisting each client to foster positive relationships with other group members.